2020
DOI: 10.3389/fpsyg.2020.00550
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mental Resilience on the Positive Coping Style of Air Force Soldiers: A Moderation- Mediation Model

Abstract: In this study, 697 air force soldiers from China were investigated with the Chinese Resilience Scale, Military Emotional Regulation Scale, Simple Coping Scale, and Social Support Rating Scale. Structural equation modeling revealed the following: (1) resilience had a positive predictive effect on active coping style; (2) the emotion regulation strategy of self-comfort mediated the relationship between resilience and positive coping style; and (3) social support moderated the latter half of the intermediary proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The association between resilience and coping styles has attracted much attention. Similarly, a study conducted among Chinese soldiers found that resilience was a positive predictor of positive coping ( 34 ). A recent study reported the positive association between resilience and positive coping based on a sample of healthcare workers during the outbreak ( 21 ).…”
Section: Introductionmentioning
confidence: 98%
“…The association between resilience and coping styles has attracted much attention. Similarly, a study conducted among Chinese soldiers found that resilience was a positive predictor of positive coping ( 34 ). A recent study reported the positive association between resilience and positive coping based on a sample of healthcare workers during the outbreak ( 21 ).…”
Section: Introductionmentioning
confidence: 98%
“…In military missions, there are various unpredictable stressful stimuli, and the stress from these stimuli can cause mental tension in soldiers and negatively affect their physical and mental health. In this way, the stress can affect the choice of different coping styles, which in turn affects the effectiveness of military missions (Romero et al, 2020;Zhao et al, 2020). Adopting a negative coping style can increase soldiers' mental stress or mental tension, solve problems negatively and passively, which tends to immerse individuals in negative emotions, reduce coping ability, and harm individual health status, as well as being detrimental to the advancement of military tasks and the improvement of troop combat effectiveness (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Coping is an individual’s cognition and behavioral effort to reduce stress and the emotional response when dealing with an incident that oversteps one’s abilities to manage adversities [ 9 ]. The coping style is a mediating variable between stress source and stress response [ 10 , 11 ]. A study [ 12 ] reported that individuals with a positive coping strategy usually had a fighting spirit and a better emotional expression performance, which was considered to indicate good psychological adjustment ability, leading to lower anxiety.…”
Section: Introductionmentioning
confidence: 99%